Pelayanan Pembayaran Pajak Kendaraan Bermotor Melalui Samsat Outlet Dalam Rangka Memudahkan Pembayaran Pajak Kendaraan Bermotor Di Samsat Outlet Plaza Metropolitan Tambun Kabupaten Bekasi - Supriyono Supriyono; Mansilla Oktaviani (Jurnal Ilmu Administrasi Publik, 2023)
The study aimed to investigate and analyze motor-vehicle tax payment service through Samsat Outlet to facilitate motor-vehicle tax payment at Samsat Outlet of Plaza Metropolitan Tambun, to investigate the obstacles faced by the officers of Samsat Outlet in enhancing the service quality of Samsat Outlet of Plaza Metropolitan Tambun Bekasi regency, and to investigate the efforts done by the officers of Samsat Outlet of Plaza Metropolitan Tambun Bekasi Regency in enhancing the service quality. The study implemented qualitative research method. The study was conducted at Samsat Outlet of Plaza Metropolitan Tambun. The data collection was done by literary study, observation, interview, and documentation technique. The result of the study showed that the motor-vehicle tax payment service through Samsat Outlet was good, but it did not run optimally. The implementation of motor-vehicle tax payment through Samsat Outlet facilitated taxpayers in arranging their taxation payments, but there were some obstacles coming from internal and external factors, one of them was lack of human resources or tax authorities in giving service to taxpayers, inadequate facilities and infrastructures, low awareness of people in paying motor- vehicle tax, long and stacked queue that extended the waiting time.